2021
DOI: 10.1364/ol.443042
|View full text |Cite
|
Sign up to set email alerts
|

Pulse repetition rate tuning of a harmonically mode-locked ring fiber laser using resonant optical injection

Abstract: We report on a new, to the best of our knowledge, technique enabling fine-tuning of the pulse repetition rate (PRR) of a soliton harmonically mode-locked (HML) fiber laser built on the nonlinear polarization evolution (NPE). Optical injection of an external continuous wave (CW) into the HML laser cavity is used for this purpose enabling precise PRR tuning with the elementary step equal to the fundamental PRR one-by-one. The effect exhibits strong resonance dependence on the CW laser wavelength and available in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
1
16
0
1
Order By: Relevance
“…1 is not so different from one used in Ref. [13]. The laser cavity consists of two types of fibers: 0.8 m length of heavily erbium-doped fiber (EDF) with normal dispersion (− 48 ps/nm/km) and standard single mode fiber (SMF-28) with anomalous dispersion (17 ps/nm/km).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 is not so different from one used in Ref. [13]. The laser cavity consists of two types of fibers: 0.8 m length of heavily erbium-doped fiber (EDF) with normal dispersion (− 48 ps/nm/km) and standard single mode fiber (SMF-28) with anomalous dispersion (17 ps/nm/km).…”
Section: Methodsmentioning
confidence: 99%
“…The effect exhibits a strong resonant dependence on the wavelength of the injected CW and makes no impact on other laser performance characteristics. We have also explored a possible application of the observed effect for precise tuning of the HML laser pulse repetition rate (PRR) [13]. Commonly, with perfect adjustment of the pump power, the number of solitons in the HML laser cavity could be changed simultaneously by a large number.…”
Section: Introductionmentioning
confidence: 99%
“…Laser sources operating at the wavelengths over 1.8 μm is of particular interest for applications in LIDARs, spectroscopy, and atmospheric analysis [11][12][13][14]. Passively mode-locked fiber lasers combining high beam quality, simplicity of adjustment, reliability, user-friendly fiber interface and relatively low cost are of great demand for these applications [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The role of background radiation as a mediator providing the equalizing interaction between pulses has been extensively discussed in this context [21,[39][40][41]. As well, the idea of manipulating HML through CW injection has been introduced and investigated [42,43], including the cases where the CW forces the laser to operate HML [39,40]. Recent studies of the transient processes in the HML laser have confirmed the importance of the pulse interaction with the background radiation in the build-up or annihilation of soliton pulses [44,45].…”
Section: Introductionmentioning
confidence: 99%